Commentaries on speeches of Cicero - Asconius Pedianus, Quintus, 9 B.C.-76 A.D (Clarendon ancient history series., 2006)
... a work of considerable utility and as such represents a fitting memorial to an under-rated scholar. - A. Keaveney, Les --Eacute--;tudes Classiques, 75,3.